2019
DOI: 10.24875/alad.19000381
|View full text |Cite
|
Sign up to set email alerts
|

Guía de práctica clínica de síndrome metabólico

Abstract: Guía de práctica clínica. Síndrome metabólico. Diagnóstico. Tratamiento timely treatment of MS as a preventive action for noncommunicable diseases; however, greater specific evidence about MS is necessary.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 25 publications
0
1
0
Order By: Relevance
“…The concentrations of the metabolic and anthropometric variables show that the participants maintain healthy values in general, which indicates they do not have metabolic risk factors or have a very low prevalence of diagnostic criteria for metabolic syndrome according to various organizations [8,29]. These values are consistent with that reported by Murguía-Romero, et al in 2015 [30] where it was found (in a 19 years old population of a metropolitan area) the variables of waist, weight, BMI, fasting glucose, TG, TC and HDL-C presented practically the same values found in this study in men and women.…”
Section: Discussionmentioning
confidence: 99%
“…The concentrations of the metabolic and anthropometric variables show that the participants maintain healthy values in general, which indicates they do not have metabolic risk factors or have a very low prevalence of diagnostic criteria for metabolic syndrome according to various organizations [8,29]. These values are consistent with that reported by Murguía-Romero, et al in 2015 [30] where it was found (in a 19 years old population of a metropolitan area) the variables of waist, weight, BMI, fasting glucose, TG, TC and HDL-C presented practically the same values found in this study in men and women.…”
Section: Discussionmentioning
confidence: 99%
“…Definitions for outcomes were: i) Type 2 diabetes (T2D)—clinical history of diabetes treatment and/or glycosylated hemoglobin (HbA1c) ≥6.5% [ 20 ]; ii) hypertension (HTN)–clinical history of antihypertensive treatment and/or SBP ≥140 mm Hg or diastolic blood pressure DBP ≥90 mm Hg during 2 separate measurements [ 21 ]; and iii) metabolic syndrome (MetS)– 3 or more of the following (using the Harmonized criteria [ 22 ]: a) elevated waist circumference of ≥94 cm in men and ≥88 cm in women [ 23 ]; b) triglycerides ≥150 mg/dL or treatment with triglyceride-lowering drugs; c) reduced high density lipoprotein (HDL) <40 mg/dL in men and <50 mg/dL in women; d) elevated blood pressure ≥130/85 mmHg or treatment with antihypertensives; and e) fasting glucose ≥100 mg/dL or treatment with glucose-lowering drugs.…”
Section: Methodsmentioning
confidence: 99%
“…Definitions for other conditions were: i) Adiposity indicators [ 24 26 ]: a) overweight (body mass index ≥25) and obesity (BMI ≥30); b) abdominal obesity—waist circumference of ≥94 cm in men and ≥88 cm in women [ 23 ]; c) elevated weight-to-height (WHtR)—≥0.5; d) body fat (free fat mass) was determined using bioimpedance [ 27 ] with increased body fat defined as ≥25% for men and ≥30% for women; e) visceral adiposity index (VAI) was calculated using a model of adipose distribution corrected for triglyceride and HDL levels [ 23 ] with high VAI according to age defined as—age <30 –VAI >2.52; age ≥30 & <42 –VAI >2.23; age ≥42 & <52 –VAI >1.92; age ≥52 & <66 –VAI >1.93; age ≥66 –VAI >2; ii) elevated cholesterol ≥200 mg/dl; iii) elevated triglycerides ≥150 mg/dL; iv) low HDL <40 mg/dl in men and <50 mg/dl in women; v) insulin resistance–Homeostatic Model Assessment (HOMA) index >2.5 [ 28 , 29 ]; and vi) and previous medical diagnosis (personal history) of heart attack or stroke. Occupation was categorised into 3 categories: agricultural workers, non-agricultural workers, and household chores.…”
Section: Methodsmentioning
confidence: 99%